Sobre Transformações Algébricas - AZEVEDO, Lenildo Moraes de (2023)
In this work we present some interesting properties of algebraic equations. More specifically, we study how the roots of a polynomial equation change when we perform some algebraic transfor- mations on them, including: additive transformations, multiplicative transformations and reciprocal transformations.